“Sugar-Sweetened Beverages” Is an Independent Risk From Pancreatic Cancer: Based on Half a Million Asian Cohort Followed for 25 Years - Chen, Chien Hua; Tsai, Min Kuang; Lee, June Han; Lin, Ro-Ting; Hsu, Chung Y.; Wen, Christopher; Wu, Xifeng; Chu, Ta-Wei; Wen, Chi Pang (Frontiers in Oncology, 2022)
Although the link between sugar-sweetened beverages (SSB) and pancreatic cancer has been suggested for its insulin-stimulating connection, most epidemiological studies showed inconclusive relationship. Whether the result was limited by sample size is explored. This prospective study followed 491,929 adults, consisting of 235,427 men and 256,502 women (mean age: 39.9, standard deviation: 13.2), from a health surveillance program and there were 523 pancreatic cancer deaths between 1994 and 2017. The individual’s IDs of the cohort were matched with National Death file for mortality, and Cox models were used to assess the risk. The amount of SSB intake was recorded based on the average consumption in the month before interview by a structured questionnaire. We classified the amount of SSB intake into 4 categories: 0 - < 0.5 serving/day, ≥ 0.5 - < 1 serving per day, ≥ 1 - < 2 servings per day, and ≥ 2 servings per day. One serving of SSB contains 12 oz with 35 g of sugar. We referred to the age and the variables at cohort enrollment for the reported risks of pancreatic cancers. The cohort was divided into 3 age groups, 20-39, 40-59 and ≥ 60. We found young people (age <40) had more prevalence and frequency of sugar-sweetened beverages than the elderly. Those consuming 2 servings/day had a 50% increase in pancreatic cancer mortality (HR=1.55, 95% CI: 1.08-2.24) for the total cohort, but a 3-fold increase (HR: 3.09, 95% CI: 1.44-6.62) for the young. The risk started at 1 serving every other day, with a dose-effect relationship. The association of SSB intake ≥ 2 servings/day with the mortality of pancreatic cancer among the total cohort was significant for those excluding smoking or diabetes (HR: 2.12, 97% CI: 1.26-3.57), obesity (HR: 1.57, 95% CI: 1.08-2.30), hypertension (HR: 1.90, 95% CI: 1.20-3.00), or those died within 3 years after enrollment (HR: 1.67, 95% CI: 1.15-2.45). Risks remained in the sensitivity analyses, implying its independent nature. We concluded frequent drinking of SSB increased pancreatic cancer in adults, with highest risk among young people.